2014
DOI: 10.1080/15374416.2014.940622
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Peer Rejection During Early Childhood

Abstract: Objective The development and course of the subtypes of peer victimization is a relatively understudied topic despite the association of victimization with important developmental and clinical outcomes. Moreover, understanding potential predictors, such as peer rejection and emotion regulation, in early childhood may be especially important to elucidate possible bi-directional pathways between relational and physical victimization and rejection. The current study (N = 97) was designed to explore several gaps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 75 publications
6
49
0
8
Order By: Relevance
“…Different mediating effects were found for the two forms of peer victimization and for ADHD and ODD symptomatology. The distinct mediating effects are consistent with the broader developmental literature (e.g., Godleski et al, ) and suggest that physical and relational victimization should be considered as separate social experiences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Different mediating effects were found for the two forms of peer victimization and for ADHD and ODD symptomatology. The distinct mediating effects are consistent with the broader developmental literature (e.g., Godleski et al, ) and suggest that physical and relational victimization should be considered as separate social experiences.…”
Section: Discussionsupporting
confidence: 85%
“…Whereas physical victimization is more commonly experienced by boys and reduces in frequency as children age, relational victimization is experienced equally by girls and boys and increases in frequency during early adolescence (Casper & Card, ). Distinct risk factors for physical and relational victimization also have been found (e.g., Casper & Card, ; Cullerton‐Sen & Crick ; Godleski, Kamper, Ostrov, Hart, & Blakely‐McClure, ; Ostrov, ). Yet, despite these important distinctions, researchers have not examined within a mixed‐gender clinical sample whether ADHD symptoms are associated with risk for both forms of victimization.…”
Section: Introductionmentioning
confidence: 95%
“…Attrition was low within the study with 85% of participants continuing participation during time 2. Children who left the study were those families who moved away (for further details on the sample, see Godleski, Kamper, Ostrov, Hart, & Blakely‐McClure, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, fewer and more contrasting results are available for children in the other roles, with followers of the bully, victims, and outsiders showing unclear patterns of social preference (Camodeca et al, 2015;Monks et al, 2002). Only one study found peer rejection to be associated with victimization (Godleski et al, 2015).…”
Section: Camodeca and Coppolamentioning
confidence: 99%
“…Although the association between some participant bullying roles and emotion understanding in preschool children has been investigated in the literature (Belacchi & Farina, ; Camodeca & Coppola, ), little evidence is available regarding the role of emotion regulation. To the best of our knowledge, only one study addressed emotion regulation in young aggressive and victimized children, finding that victimization was associated with emotion dysregulation, both cross‐sectionally and longitudinally, but no associations were found for aggressive behavior (Godleski, Kamper, Ostrov, Hart, & Blakely‐McClure, ). In this study, emotion regulation was measured with the Emotion Regulation Checklist (Shields & Cicchetti, ) that we also employed whereas aggression and victimization were assessed using observations and research assistant ratings, respectively.…”
Section: Introductionmentioning
confidence: 99%